Analysis of users need on academic library space and satisfaction / Nur Ainaa Aliaa Ahmad Latfi And Mazwani Ayu Mazlan. - Ahmad Latfi, Nur Ainaa Aliaa; Mazlan, Mazwani Ayu (Universiti Teknologi MARA Cawangan Selangor, 2018)
The aim of this paper focuses on the study on satisfaction of various library spaces that available inside the academic library of Kolej Profesional Mara Beranang, Malaysia. The study is been conducted using quantitative method in which questionnaires have been distributed to 100 respondents and all the quessionnaire have been return to be analyzed. The finding of the research that focus on the satisfaction towards four types of space which is collaboration space, individual space, interaction space and community space have give a clear picture on the level of satisfaction on the various need of space. This study is essentially suitable for the chief librarian for any types of library in doing their steps in improving the library physical in the good sense.